Nordic registry studies: healthcare use and sick leave after COVID-19 ... - Himmels, Jan; Brurberg, Kjetil Gundro; Magnusson, Karin (OSF Registries, 2024)
This systematic review aims to compile and analyse data from Scandinavian registry studies to provide a comprehensive overview of the long-term effects of COVID-19. By synthesizing evidence from the Nordic countries, Denmark, Norway, and Sweden, Finland, Iceland, the Faroe Island, Åland and Greenland this review seeks to identify common patterns and differences in long-term health outcomes, assess the burden of long COVID, and highlight gaps in current knowledge. The findings will inform healthcare providers, researchers, and policymakers about the enduring impact of COVID-19 and guide future research and healthcare strategies to mitigate its long-term effects. ...